2017
DOI: 10.3389/fpsyg.2017.01507
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Contrast in the Evaluation of Paintings Is Liked More but Remembered Less than High Contrast

Abstract: Many visual aspects of paintings, as well as exposure to art and cultural norms, contribute to the aesthetic evaluation of paintings. The current study looked at heightened visual contrast as an important factor in the appreciation of paintings. Participants evaluated abstract digitized paintings that were manipulated in contrast for an appreciation task and were later presented with these paintings in a memory task. The results indicated that for art appreciation, a moderate increase in contrast resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, one study in which subjects rated the pleasantness of printed image reproductions found that photographs with enhanced image contrast were rated as more pleasing (Pedersen et al, 2010). Also, higher contrast reproductions are better liked than the original paintings (Dijkstra and van Dongen, 2017;van Dongen and Zijlmans, 2017). Similarly, liking of photographs decreased as image contrast was reduced (Tinio et al, 2011).…”
Section: Consumer Liking and Contrastmentioning
confidence: 96%
See 1 more Smart Citation
“…However, one study in which subjects rated the pleasantness of printed image reproductions found that photographs with enhanced image contrast were rated as more pleasing (Pedersen et al, 2010). Also, higher contrast reproductions are better liked than the original paintings (Dijkstra and van Dongen, 2017;van Dongen and Zijlmans, 2017). Similarly, liking of photographs decreased as image contrast was reduced (Tinio et al, 2011).…”
Section: Consumer Liking and Contrastmentioning
confidence: 96%
“…Local image contrast involves the difference in brightness between each pixel (or dot) location and the neighboring locations. Global image contrast is the difference between light and dark areas, or the distribution of intensity levels of luminance, throughout the entire image (Dijkstra and van Dongen, 2017; Ortiz-Jaramillo et al , 2018; Pedersen et al , 2010; Simone, 2016). Given the current research’s focus on entire images appearing in social media marketing, the current study will examine effects of global image contrast.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One possible explanation is that AOI 2 contains high bright-dark contrasts and therefore is easier to memorize. A study by Dijkstra and van Dongen (2017) found that abstract paintings, when manipulated with high contrasts, were better stored in the memory. Paintings that were manipulated with a moderate contrast revealed the highest appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…The oddball paradigm is often used in the investigation of ERP components due to its success in evoking robust and reliable markers of cognitive function, particularly the P300 component 34 . In addition, because the level of attraction can cause people's emotional changes, the oddball paradigm was utilized in order to identify differences in neural responses between attractive and unattractive 35 . N2 refers to the negative ERP component appearing between about 200 and 300 ms after stimulus onset.…”
Section: Introductionmentioning
confidence: 99%